Lonchocarpus verticillatus (Leguminosae-Papilionoideae): A new species from Seasonally Dry Tropical Forest in Colombia - Ariza Cortés, William; Rivera, Cristiam; Zapata, Diego (Phytotaxa, 2023)
Lonchocarpus verticillatus (Leguminosae, Papilionoideae, Millettieae) is described and illustrated from the seasonally dry forests of the Cauca River valley in Antioquia department, northwestern Colombia. This species is clearly distinguished from other species of the genus by its notably whorled arrangement of leaves, up to 17 leaflets, mesophyll and calyx with glandular dots, and lax inflorescences up to 31 cm long. It is a tree reaching up to 25 m in height, inhabiting forest remnants. Isolated trees can be found in pastures dedicated to livestock. It has been recorded at elevations ranging from 250 to 670 m. Due to habitat fragmentation, the increasing development of infrastructure in its occurrence area, and the limited number of records, a preliminary recommendation is to categorize it as ‘Endangered’ (EN) according to the IUCN criteria.